Who Could ‘the Godless Ishmaelites from the Yathrib Desert’ Be to the Author of the Novgorod First Chronicle? The "Apocalypse of Pseudo-Methodius" in Medieval South and East Slavic Literatures - Brzozowska, Zofia Aleksandra (Studia Ceranea, 2019)
The work of Pseudo-Methodius, whose creation (in the original Syrian version) dates back to ca. 690, enjoyed considerable popularity in Medieval Slavic literatures. It was translated into Church Slavic thrice. In all likelihood, these translations arose independently of each other in Bulgaria, based on the Greek translation, the so-called ‘first Byzantine redaction’ (from the beginning of the 8th century). From Bulgaria, the Slavic version of the Apocalypse of Pseudo-Methodius spread to other Slavic lands – Serbia and Rus’. In the latter, the work of Pseudo-Methodius must have been known already at the beginning of the 12th century, given that quotations from it appear in the Russian Primary Chronicle (from the second decade of the 12th century). In the 15th century, an original, expanded with inserts taken from other works, Slavic version also came into being, known as the ‘interpolated redaction’. All of the Slavic translations display clear marks of the events that preceded them and the circumstances of the period in which they arose. Above all, the Saracens – present in the original version of the prophecy – were replaced by other nations: in the Novgorod First Chronicle we find the Mongols/Tatars (who conquered Rus’ in the first half of the 13th century).